Retroperitoneal lymphadenopathy in familial Mediterranean fever. Issue 768 (October 1989) - Rimon, D.; Meir, Y.; Cohen, L.
Abstract : Peripheral lymphadenopathy is rarely observed, whereas mesenteric lymphadenopathy is found occasionally on laparotomies in patients with familial Mediterranean fever (FMF). Retroperitoneal lymphadenopathy was reported only once in an autopsy of a patient with FMF. Our case is the second one, and the first one to be diagnosed during life, by means of abdominal ultrasonography and computerized tomography. In patients with FMF, where lymph node biopsy was done, the pathological finding was non-specific lymphoid hyperplasia.